KEPEMIMPINAN TRANSFORMASIONAL, KEPEMIMPINAN TRANSAKSIONAL DAN BUDAYA ORGANISASI - Wenny Hestika (Universitas Riau, 2017)
Abstract: Transformational Leadership, Transactional Leadership and OrganizationalCulture. The purpose of this study to determine and analyze the effect of transformational leadershipand transactional leadership on organizational culture in rural credit banks Local CompanyRokan Hulu. This study uses a quantitative approach with a population of 35 respondents. Thetechnique of collecting data through questionnaires and observation. Analysis of data using multiplelinear regression. Contribution of the independent variable (X) on the dependent variable(Y) that is equal to 54.9%. This shows that transformational leadership and transactional leadershipaffect the Company’s organizational culture Regional Rural Banks Rokan Hulu.